PENGEMBANGAN KEPUASAN KERJA KURIR JASA EKSPEDISI YANG DITINJAU DARI KEBIJAKAN MOTIVASI KERJA DAN BUDAYA ORGANISASI - Fatria Maulana Ibrahim; Mochamad Vrans Romi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Data shows that job satisfaction among couriers is declining, which suggests that technological and scientific advances require high-quality talent. Factors affecting job satisfaction include work motivation and organizational culture. The aim of this research is to find out how work motivation and organizational culture influence job satisfaction in delivery services. Using a saturated sample, 48 couriers were registered as respondents. This quantitative research was conducted using double regression data analysis supported by SPSS version 26 and data collection through documentation, interviews, and questionnaires. According to this study, job motivation has no effect on courier job satisfaction. However, organizational culture has an influence on the satisfaction of the courier.